Quantization of Higher Dimensional Linear Dilaton Black Hole Area/Entropy From Quasinormal Modes - Sakallı, İzzet (International Journal of Modern Physics A, World Scientific Publishing, 2013)
The quantum spectra of area and entropy of higher dimensional linear dilaton black holes in various theories via the quasinormal modes method are studied. It is shown that quasinormal modes of these black holes can reveal themselves when a specific condition holds. Finally, we obtain that a higher dimensional linear dilaton black hole has equidistant area and entropy spectra, and both of them are independent on the spacetime dimension.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1142/S0217751X13920024) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; hawking radiation; Quasinormal Modes